Student’s Perceptions Regarding Assessment Changes in a Fluid Mechanics Course - Sena-Esteves, Teresa; Morais, Cristina; Guedes, Anabela; Brás Pereira, Isabel; Marques Ribeiro, Margarida; Soares, Filomena; Pinto Leão, Celina (Education sciences, 2019)
The main objective of this study is to evaluate students’ perceptions regarding different methods of assessment and which teaching/learning methodologies may be the most effective in a Fluid Transport System course. The impact of the changes in the assessment methodology in the final students’ grades and attendance at theoretical classes is also analysed, and the results show that students’ attendance at theoretical classes changed significantly. The students prefer and consider more beneficial for their learning assessment through several questions/problems and small tests during theoretical lessons instead of a single moment of evaluation. For them, the traditional teaching/learning methodology is still considered the most effective one. At the same time, students perceive that the development of the Practical Work (PW) and several moments of assessment had positive repercussions on the way they focus on the course content and keep up with the subjects taught, providing knowledge on the area under study, encouraging collaborative work and stimulating the students’ intellectual curiosity. Largely, students agree that the PW is an important tool in their learning process and recommend it as a teaching activity. In general, students are confident with the knowledge acquired with the PW and feel able to size fluid transport systems.